Teachers' views on assessment and evaluation methods in STEM education: A science course example - Ferhat Karakaya; Mehmet Yılmaz (Journal of Pedagogical Research, 2022)
There have been significant advances in science and technology in recent years. Therefore, all countries need qualified people who can take on the challenges of life today and compete in the international arena. This has led countries to adopt new approaches to education. STEM education is one of the latest examples of those approaches. This study investigated science teachers' views on assessment and evaluation methods in STEM education. The study adopted a phenomenology design. The sample consisted of 22 science teachers from public or private schools in different provinces in Turkey in the 2021-2022 academic year. All participants were experienced in STEM education. Data were collected using a semi-structured interview questionnaire developed by the researchers. The study had two significant results. First, participants used process- and outcome-oriented methods to evaluate STEM education. Second, they made some errors and faced some challenges in evaluating STEM education. However, those errors and challenges were of teacher or education system origin. Therefore, schools should provide teachers with in-service training on assessment and evaluation methods in STEM education, and educators should develop different measurement tools to help teachers make fewer errors and overcome the challenges they face in evaluating STEM education.